The research trend of the undergraduate seminar papers of the University of the Philippines Manila, College of Dentistry (UPCD) From 1999-2013 - Aman, Angeline Beatrice L.; Reyes, Veronica M.; Sy, Chanel Isseline D.
The University of the Philippines Manila supports the state's effort to advance the health of the Filipinos by improving the country's aptitude for health research and development. Research encourages the continued progress of the entire higher education sector. For this reason, it is vital for us to scrutinize the quantity and quality of undergraduate researches being produced per year, and see how these have changed. Our aim is to determine the research trend of the UPCD undergraduate seminar papers from 1999 to 2013. A similar study published in Brazil on 2011 by Scariot, Stadler, Assuncao, Pintarelli, and Ferreira titled "A Map of Brazilian Dental Research in the Last Decade" is being modelled by this paper.